The promise : never have another negative thought again - Price, Graham W. (Pearson, 2013)
You can eliminate anxiety, worry and negativity from your life - that's what The Promise is all about. It's powerful, inspiringand revolutionaryprogramthat will turn all your negative thoughts into feelings of positivity and wellbeing. It's a change you will feel in every part of your life andone your friends, family and colleagues will see. Soon you'll begin to livethelife you've always wanted. That's The Promise.